Infinitival before and after-clauses in European Portuguese : temporal and aspectual properties - Silvano, Purificação; Cunha, Luís Filipe (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
The main goal of this paper is to discuss temporal and aspectual features of sentences with clauses introduced by the connectives antes de + Infinitivo (‘before’ + Infinitive) and depois de + Infinitivo (‘after’ + Infinitive) combined with situations in the Pretérito Perfeito in European Portuguese. Our discussion is based on the widespread view that these clauses are locating adverbials (cf. Kamp and Reyle (1993)) with temporal information of anteriority, in the case of antes de, and posteriority, in the case of depois de. However, this analysis is not as straightforward as one would expect, because, while before-clauses consistently render the same temporal relation (of anteriority), after-clauses may convey a temporal relation of inclusion, in addition to the standard posteriority relation. We put forward the hypothesis that aspectual characteristics play an important role in these differences, insofar as allowing a temporal reading that at first sight is not predicted from the semantic nature of the connective. In order to maintain a uniform treatment of before and after-clauses with respect to their temporal features, accounting simultaneously for the differences that emerge in their linguistic behaviour, we claim, along with Beaver & Condoravdi (2003) and Condoravdi (2010), that the locating time interval provided by these clauses is bounded to the left, but not to the right, that is, what is focused is the initial frontier of the situation that provides the time interval, leaving the final one undetermined. Furthermore, we show that, although the temporal mechanisms are parallel, the interference of aspectual properties leads to interesting differences in the final interpretation of before and after-sentences.